(untitled) (Economic and Political Thought, 2017)
The paper aims to present the image of Poland’s neighbours, namely: Russia, Ukraine and Germany, presented in the Polish media between July and December 2013. To obtain a possibly complete final image, a database of textual news articles was created, and its content was gathered from many various on-line sources, chosen due to their popularity and wide spectrum of political views. The preliminary dataset consisted of 8096 articles. The analysis of the final dataset was conducted by applying a mixed-method methodology, employing CAQDAS (QDA Data Miner and Wordstat). The results of the analysis showed that all the Polish media were focused mainly on neighbouring countries and tended to depict them in rather dark colours; moreover, a surprisingly large share of statements mentioning Germany, Russia and Ukraine were focused on historical issues, mainly of the Second World War period. The results of the research lead to emergence of new research hypotheses: to what extent the image of foreign countries was a reflection of social moods in 2013 and an indicator of the upcoming parliamentary and presidential election results? Was it mainly a product of the publishers aiming to influence the readers’ political choices? Regardless of which of the above hypotheses is true, it can be assumed that the media image could be applied in the prediction and analysis of international relations strategies employed in particular countries. Evidence for the reasonableness of this hypothesis is provided by the analysis of the current priorities of public diplomacy in Poland.